Prevalence of depression and its potential contributing factors in patients with enterostomy: A meta-analytical review - Tang, Wymann Shao Wen; Chiang, Li Ling Christine; Kwang, Kay Wee; Zhang, Melvyn Wei Bin (Frontiers in Psychiatry, 2022)
Objective: In patients with intestinal pathologies, the placement of a stoma bag affects multiple aspects of their perceived quality of life. This meta-analysis aims to evaluate the prevalence of depression amongst patients with enterostomies and to determine underlying moderators to explain potential heterogeneity of prevalence. Methods: Relevant published studies were identified by searching PubMed, Embase, PsycINFO, Cochrane, CINAHL, Scopus and Web of Science until May 2022. The random-effects model was used to determine the pooled prevalence of depression among patients with enterostomies using cross-sectional studies from various countries. Meta-regression and subgroup analysis were performed to identify factors contributing to heterogeneity. Quality assessment of the included studies was conducted using the Newcastle-Ottawa scale for non-randomized studies. Results: The pooled prevalence of depressive symptoms among enterostomy patients using the random-effect model was 41.6% (95% confidence interval [CI]: 25.4 - 59.7%, Q value = 145.794, df= 8, p< 0.001, tau^2 =1.124, I^2 =94.513). Meta-regression was conducted which found mean age and gender to not be significant moderators for the heterogeneity in prevalence. Subgroup analysis by indications for enterostomy formation showed that prevalence of depression was highest in colorectal cancer patients at 34.4% (95% CI: 27.2 - 42.4%). Subgroup analysis by region showed that enterostomy patients in Africa had the highest prevalence of depression at 88.2% (95% CI: 76.1 - 94.6%) compared to other regions. Subgroup analysis by stoma indication was not significant. Conclusion: This meta-analysis reports that the pooled prevalence of depression amongst enterostomy patients is 41.6%. Indications for enterostomy formation and region of the cross-sectional study have been identified to be potential sources of heterogeneity. This highlights the need for appropriate psychosocial support and interventions at different stages of enterostomy placement for patients.